Evaluating the physical and insecticidal properties and the effects on grain flow properties of a synthetic amorphous zeolite intended for grain protection - Yao, Kouame Dominique (Kansas State University, 2018)
Alternatives to chemical grain protectants are needed that have low mammalian toxicity and high specificity to insects with no adverse environmental impacts. This project investigated the viability of using a synthetic amorphous zeolite as a potential alternative to chemical insecticides and phosphine in Australian grain. We evaluated the impacts of moisture content and application rates on dust and grain physical properties; compared registered dusts with this promising novel dust in terms of impact on grain flowability; investigated changes in bulk properties of inert-dust treated grain; and we constructed dynamic dewpoint isotherms of hard red winter wheat and amorphous silica dusts for a better understanding of moisture interactional behavior of the synthetic amorphous dust based on wheat initial moisture content. Full sorption isotherms of zeolite and wheat obtained at 25, 35, and 45⁰C clearly exhibited the hysteresis phenomenon. The intensity of hysteresis remained unchanged with increasing temperatures for Hard Red Winter wheat (HRW), whereas, the intensity of hysteresis decreased with increased temperatures during water adsorption for the porous synthetic amorphous zeolite powder. Considering the IUPAC classification of isotherms, HRW had typical type II sigmoid shape isotherm, whereas, zeolite powder had a sorption isotherm close to resembling a type IV sigmoid shape isotherm. The hysteresis loops were of type H3 for HRW, and of type H4 for zeolite powder. Irrespective of sorption direction, DLP model was the best model to estimate zeolite and HRW sorption isotherms, followed by GAB and BET models, although BET model provided almost perfect fitting to sorption data in the water activity range 0-0.5. Particle size of the amorphous dust increased with increasing moisture content. Conversely, shape parameters (circularity, aspect ratio, convexity, and solidity) generally decreased with increasing dust moisture contents. When wheat was mixed with the amorphous dust at different rates and moisture levels, the bulk density of wheat decreased, while the tapped density and the angle of repose increased, resulting in higher Hausner ratios and Carr Index values. Treating wheat with the amorphous dust caused the treated wheat to transition from an acceptable flowability to a poor flowability, based on angle of repose, Hausner ratio, and Carr index data, which do not account for the interaction of wheat with the storage vessel. Our data suggest that a range of moisture content (2-6%) and an application rate (0.5 g/kg) mitigate the adverse effects on wheat flowability. However, based on flow rate index and specific energy requirements, flowability of wheat was generally enhanced by admixing wheat with the amorphous dusts. Wheat treated with Odor-Z-Way was comparable with wheat treated with Celite or Diafil as they all exhibited low cohesion, moderate permeability, and moderate sensitivity to aeration. Wheat treated with each of the three dusts became almost unstable due to segregation, moisture uptake, lower adhesion, and coating of the blade and test vessel. A decrease in bulk density was however observed, although the decrease was smaller when wheat was admixed with Odor-Z-Way. The susceptibility to Celite, Diafil, and Odor-Z-Way varied among stored-product insect species and also among the type of substrate (wheat or concrete). Adults of the lesser grain borer, Rhyzopertha dominica, were generally least susceptible to all three amorphous silica dusts; however, a complete suppression of progeny production was possible using Celite. Adult emergence was generally not prevented by Celite, Diafil, and Odor-Z-Way which suggested a lower insecticidal efficacy of the three dusts against early developmental stages. On concrete, Odor-Z-way was particularly effective at controlling all stored-product insect species after 24 h of exposure. In view of the bulk and dynamic flow properties and the insecticidal activity, Odor-Z-Way has potential to become a grain protectant provided that segregation and the decrease in bulk density are mitigated and that the insecticidal activity is not adversely affected by the seemingly low adhesion on wheat kernels.
Keywords: Agriculture; Wheat; Stored-product entomology; Chemical engineering; Agricultural and biological engineering; Inert dust technology to protect grain during transport and storage